Empowering Digitalization: Nurturing Content Creators for Enhanced Soft Skills - Suhendro Busno; Moch Alfan Rosyid; Ade Eviyanti (Indonesian Journal of Cultural and Community Development, 2023)
The burgeoning wave of digitalization has pervaded diverse sectors, catalyzing transformative impacts on economics, society, and education. This study investigates the pivotal role of content creators in propelling digital marketing endeavors, fueled by the amplification of internet accessibility and technological infrastructure. Leveraging the potential of this trend, a community service initiative was undertaken to impart soft skill training to students at SMK Muhammadiyah 1 Taman Sidoarjo. Employing a methodological approach encompassing content creator awareness, module development, laboratory training, and post-training assessment, this research seeks to equip students with essential competencies. Results showcase the potency of content creators as linchpins in the digital landscape, elucidating their significance in disseminating educational and engaging content. The implications of this endeavor reverberate globally, underscoring the critical synergy between digitalization and content creation for sustainable advancements across sectors. Highlight: Multisectoral Impact: Digitalization's pervasive influence across economics, society, and education drives transformative change. Content Creator Significance: Investigates content creators' pivotal role in fueling digital marketing via amplified internet access and tech infrastructure. Soft Skill Empowerment: Community initiative imparts crucial competencies to students, employing a structured methodology for effective learning. Keyword: Digitalization, Content Creators, Soft Skill Training, Internet Accessibility, Technological Infrastructure